Gerhard Ebeling oor geloof - Wyk, Gabriël M. J.van (HTS teologiese studies, 2016)
Gerhard Ebeling on faith. Gerhard Ebeling (1912–2001), not only the foremost Luther researcher of the previous century but also one of the most prominent contributors to protestant theology during that period, wrote extensively about faith throughout his long and productive life as a professional theologian. He learnt from Luther that discerning judgement in the differentiation of related matters forms the basis of all sound theology. Applying this insight to his own thought, he reflects on the development of the phenomenon of faith in the Old Testament community and early Christianity and the formalisation of the concept for use in the domain of religious studies. He defends the argument that Christian faith is not only faith in Jesus as the Christ and Lord but also that Jesus, and He only, is the founder and perfecter of faith. The concept of faith is also explored by Ebeling in relation to love, life and reason. The article concludes with a critical evaluation of Ebeling’s contribution in guiding us to witness authentically about our own faith in Jesus Christ within our own situation and against the background of the problems it poses for believing in Christ.